Perbandingan pemberian air kelapa muda (cocos nucifera l) dengan isotonik terhadap denyut nadi dan VO2maks atlet remaja - Hatta, Muhammad; Susanto, Hardhono; Rahfilludin, M. Zen (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: Football players requires a high level of VO2max which is influenced by the available of energy. Tender coconut water and branded isotonic are as energy drinks containing of carbohydrates and the body’s electrolyte ions that can prevent dehydration. The increasing pulse describes a the condition of dehydrated players during match or training. Objective: To Examine comparison of tender hybrid coconut water and branded isotonic to pulse and the plyer’s level of VO2max in the Diponegoro University Football School in Tembalang, Semarang. Methods: Experimental study with an approach of randomized pretest - post test control group design at 41 soccer’s player aged 13-15 years at Diponegoro University Football School Tembalang in August 2015. The treatment group consumed consumed 250 mL tender coconut water (n=13) and branded isotonic (n=14) and group control consumed mineral water (n=14) every 15-30 minutes for 5 times. Observation  pre test and post test 1,2,3 with interval of 3 day after physical training, athlets test the pulse to palpation techniques for 15 seconds and VO2max test with multistage fitness test. Result: The VO2max and pulse recovery in the beginning of research for 3 group was similar (p = 0,454 and p = 0,294). Post test 1 VO2max on three group are same (p = 0,841) but the recovery pulse is better on the group of tender coconut water and branded isotonic (p = 0.006). Post test 2, VO2max and recovery pulse is more good by players who were given tender hybrid coconut water and branded isotonic (p = 0,004 and p = 0,017), as the same post test 3 VO2max and recovery pulse (p = 0.000 and p = 0,004).Conclusion: Giving the tender hybrid coconut water and branded isotonic to same to recovery pulse and increased VO2maks on athlete school football diponegoro unversity